ABUSE AGAINST CHILDREN IN IRAQ - Manal Lueibi Tarish; Nabil Omran Moussa (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study deals with the pattern of violence that parents issue over their children has received more attention than patterns of family violence, The child protection policy is considered one of the important policies to draw the country’s vision and advance the reality of the Iraqi child, there are many violations committed against children, so what is the role of the child protection policy in limiting this phenomenon or at least reducing it, also the study dealt with a phenomenon that violates the most basic human rights of the child, a crime punishable and a direct or indirect cause of other crimes, it threatens the unity of the basic structure of society and the family, before that it violated the rights of the child and violated international human rights instruments concerned with human rights, the family in general and the child in particular. The current study attempts to present a set of aims which is treating the phenomenon of physical violence against children in Iraqi society among the most prominent of these aims is: To identify the differences in the independence of the forms of physical violence practiced by the father and mother on the child depending on the gender of a child. The study has reached many results: Widespread violence against children, the most common is physical violence, it notes that physical violence is associated with other patterns of violence, so many types of violence are accompanied by physical violence. The study recommendations: Activate child protection laws stipulated in the Convention on the Rights of the Child, work for punishing abusive children, coordinate with civil society and all state institutions to protect childhood, because children are the future of every nation.